2018
DOI: 10.1371/journal.pone.0206941
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-scale understanding of relationship between homo-repeat enrichments and protein aggregation properties

Abstract: Expansion of homo-repeats is a molecular basis for human neurological diseases. We are the first who studied the influence of homo-repeats with lengths larger than four amino acid residues on the aggregation properties of 1449683 proteins across 122 eukaryotic and bacterial proteomes. Only 15% of proteins (215481) include homo-repeats of such length. We demonstrated that RNA-binding proteins with a prion-like domain are enriched with homo-repeats in comparison with other non-redundant protein sequences and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…It is known from the literature that a change in the pH of the solution stimulates protein conformational changes, which leads to aggregation [ 31 , 32 ]. The amyloidogenic peptides that we predicted form amyloids, which is associated with the presence of amyloidogenic motifs [ 33 ] and their high percentage compared to in the whole protein S1. For a protein containing several immunoglobulin-like (Ig-like) domains, it was shown that high identity may be associated with a higher probability of the misfolding of this protein and a tendency to aggregation, including fibrils [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known from the literature that a change in the pH of the solution stimulates protein conformational changes, which leads to aggregation [ 31 , 32 ]. The amyloidogenic peptides that we predicted form amyloids, which is associated with the presence of amyloidogenic motifs [ 33 ] and their high percentage compared to in the whole protein S1. For a protein containing several immunoglobulin-like (Ig-like) domains, it was shown that high identity may be associated with a higher probability of the misfolding of this protein and a tendency to aggregation, including fibrils [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Massa molar (136)(137)(138)(139) 311,7990 g/mol Penampilan (140)(141)(142) Kristal tidak bewarna Bau (143)(144)(145) Tidak Berbau…”
Section: Sifat Kimiaunclassified